2000
DOI: 10.1088/0953-4075/33/22/309
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-UV absorption spectrum of a laser-produced chromium plasma: 3p-subshell photoabsorption by Cr2+ions

Abstract: The dual laser plasma photoabsorption technique has been used to measure the time-resolved vacuum-UV photoabsorption spectrum of a chromium plasma. Resonant photoabsorption cross sections, constructed with the aid of Hartree-Fock calculations, and weighted in accordance with the plasma temperature, have been used to produce the synthetic Cr2+ spectra. The relevant plasma temperature and ionization balance are obtained from simple analytical models for various times during the expansion phase of the plasma plum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…The theoretical data have been shifted by +0.75 eV to fit the 3p − 4s resonances of the experimental spectrum. Comparing these data with observation, it is seen that the relative contributions expected for a plasma electron temperature (T e ) of 2.5 eV fit the experimental data quite well and compare favourably with the temperature quoted for Cr 2+ (T e = 3.3 eV) [3]. This accounts for the presence of metastables in the plasma which contribute to the photoabsorption spectrum of Mn 2+ recorded here.…”
Section: +supporting
confidence: 82%
See 3 more Smart Citations
“…The theoretical data have been shifted by +0.75 eV to fit the 3p − 4s resonances of the experimental spectrum. Comparing these data with observation, it is seen that the relative contributions expected for a plasma electron temperature (T e ) of 2.5 eV fit the experimental data quite well and compare favourably with the temperature quoted for Cr 2+ (T e = 3.3 eV) [3]. This accounts for the presence of metastables in the plasma which contribute to the photoabsorption spectrum of Mn 2+ recorded here.…”
Section: +supporting
confidence: 82%
“…The 3p→ns (n ≥ 5) and the 3p→4d transitions occur at higher energies than experimentally recorded here. As was observed in [3] for Cr 2+ (which is isoelectronic with Mn 3+ ), photoabsorption from states of the 3d 3 4s configuration does not play a significant role in determining the overall shape and structure of the experimental photoabsorption spectrum and they are therefore omitted from this figure. Fig.…”
Section: +mentioning
confidence: 92%
See 2 more Smart Citations
“…Our investigations using 35-fs pulses showed that the 29th harmonic (λ = 27.6 nm, E ph ≈ 45.1 eV) is enhanced at the leading edge of the strong spectral band of the 3p 3d transitions of chromium ions. At the same time, previous investigations of the photoabsorption and photoionization spectra of chromium plasma in the region from 41 to 42 eV showed the existence of transitions with high oscillator strengths, which can be responsible for the strong absorption (in particular, of the 27th harmonic) [43][44][45]. These and other studies of the photoabsorption spectra of chromium allowed one to identify the ranges of strong absorption in the FUV region.…”
Section: Resonance Enhancement Of Individual Harmonicsmentioning
confidence: 60%